Punctuated Lives: Abortion, Ellipses, and Parentheses in Annie Ernaux's L'événement (2000) and Line Papin's Une vie possible (2022). - Nevin, Matilda (Esprit Createur)
This article examines the representation of abortion in two autobiographical texts: Annie Ernaux's L'événement (2000) and Line Papin's Une vie possible (2022). Analyzing their use of punctuation particularly parentheses and ellipses it argues that Papin inherits an aesthetics of hesitation from Ernaux an aesthetics that allows both writers to make space for others' experiences of abortion.